Strategic Approaches for Achieving Adiwiyata School Status: Insights into the Principal's Role - Mahmud, Muchammad Eka (JURNAL AL-TANZIM, 2023)
This research aims to analyze the principal's strategy in realizing Adiwiyata schools and describe the planning, organization, and control of the Adiwiyata program at MAN 1 Samarinda and MAN 2 Kutai Kartanegara. The research uses a qualitative method with a descriptive approach; the data source is words with two data used, primary and secondary data. Techniques for collecting data include interviews, observation, and documentation, as well as testing the validity of the data in the form of data triangulation, technical triangulation, and source triangulation. The data analysis technique uses the theories of Miles, Huberman, and Saldana, and then the researcher uses data coding to present and verify the data. The results of the research show that the head of the madrasah makes planning and supervision of the Adiwiyata program, forms an Adiwiyata committee team and instills Adiwiyata values, completes facilities and infrastructure, makes policies, collaborates with various parties, and guides several schools. This research provides implications regarding the importance of the critical role of madrasah heads in realizing Adiwiyata status in schools. This emphasizes the vital role of the school principal in providing direction, vision, and strategies to integrate Adiwiyata values into the school environment as a whole.